Evaluation of Computation and Revenue Collection Obligation for Land and Building Acquisition Rights (BPHTB) for the Purchase of Land and Buildings in Cirebon City, 2023 (Study at the Notary & PPAT Office of DR. Hj. ARIN, S.H., M.M., M.Kn.) - DWI YANTHI, WINDA; Suwandi, Suwandi; Silviana, Vega (Jurnal Ekuisci, 2024)
This study was performed at the Notary & PPAT office of DR. Hj. ARIN, S.H., M.M., M.Kn. This study is to examine the function of Notary & PPAT DR. Hj. ARIN, S.H., M.M., M.Kn. I will discuss the challenges and issues encountered in the collection of land and building purchase fees in Cirebon City, as well as the efforts undertaken to address them. This study employs a qualitative research methodology with a descriptive approach to elucidate the implementation of BPHTB collection issues. This is subsequently examined based on scientific principles and theories, leading to a final result. The findings of this study indicate that the BPHTB calculations at the Notary & PPAT office of DR. Hj. ARIN, S.H., M.M., M.Kn are in accordance with the stipulations of Law No. 28 of 2009. These requirements are applicable to all Notaries and PPAT in Cirebon City. The calculation and collection of BPHTB for land and building transactions in Cirebon City utilize a self-assessment system via the e-BPHTB online platform.